BEHAVIOURAL, MORPHOLOGICAL AND CHROMATOPHORIC ALTERATIONS INDUCED BY ARSENITE EXPOSURE IN FRESHWATER FISH, CHANNA PUNCTATUS (BLOCH.) - SHRADDHA DWIVEDI; SUNIL P. TRIVEDI (International Journal of Pharma and Bio Sciences, 2015)
Present investigation aims to evaluate arsenite toxicity in terms of behavioural, morphological and chromatophoric alterations in fish, Channa punctatus. 10 days acclimatized fish were divided into control and three experimental groups having 10 fish. In the experimental groups, fish were exposed to three different concentrations of arsenite (15, 30 and 60 mg/l). The behavioural and morphological alterations were recorded with 10 hr observation per day during 96 h for control and experimental groups. Results clearly depict prominent behavioural changes such as hyper excitability, jumping, restlessness, imbalanced swimming, fin movement, mortality and gulping of air at surface in different arsenite exposed groups contrast to control. Similarly, altered morphological parameters viz., discoloration of skin, lesions on skin, shedding of scales, excessive mucus secretion, and muscular bleeding was also recorded on arsenite exposure. The investigation of scales clearly shows an aggregation of pigment granules in arsenite exposed groups in a concentration dependent manner.